Cognitive function in early onset schizophrenia: a selective review - Frangou, Sophia (Frontiers in Human Neuroscience, 2010)
Schizophrenia is widely regarded as the clinical outcome of aberrant neurodevelopment caused by a combination of genetic and non-genetic factors. Early Onset Schizophrenia (EOS) manifests in childhood or adolescence and represents a more severe variant of the Adult Onset form of the disorder (AOS). EOS offers a unique opportunity of exploring the impact of disease related mechanisms on the developmental trajectory of cognitive function. The present review focused on the domains of general intellectual ability (IQ), attention, executive function and memory. Significant methodological variability was noted across the different studies that examined these aspects of cognition in EOS patients. Despite this, a consistent pattern emergent from the data suggesting that (a) EOS patients compared to healthy children and adolescents show impairments of medium to large effect size in IQ, attention, memory and executive function (b) despite increased clinical severity, the cognitive profile of EOS patients is comparable to that of AOS patients (c) healthy adolescents show age-related improvement in their ability to perform tests of attention, memory and executive function; this is not present in EOS patients thus resulting in increased age-related deviance in patients’ performance. This apparent decline is mostly attributable to patients’ failure to acquire new information and to use more sophisticated cognitive strategies.